A role for the carbohydrate portion of ginsenoside Rg3 in Na+ channel inhibition - Kim, J.-H.; Hong, Y.-H.; Lee, J.-H.; Kim, D.-H.; Nam, G.; Jeong, S.M.; Lee, B.-H.; Lee, S.-M.; Nah, S.-Y. (KOREAN SOC MOLECULAR & CELLULAR BIOLOGY, 2005)
We showed recently that ginsenosides inhibit the activity of various types of ion channel. Here we have investigated the role of the carbohydrate component of ginsenoside Rg3 in the inhibition of Na+ channels. The channels were expressed in Xenopus oocytes by injecting cRNAs encoding rat brain Nav1.2α and β1 subunits, and analyzed by the two-electrode voltage clamp technique. Treatment with Rg3 reversibly inhibited the inward Na+ peak current (INa) with an IC50 of 32.2 ± 4.5 μM, and the inhibition was voltage-dependent. To examine the role of the sugar moiety, we prepared a straight chain form of the second glucose and a conjugate of this glucose with 3-(4-hydroxyphenyl) propionic acid hydrazide (HPPH). Neither derivative inhibited INa. Treatment with the carbohydrate portion of ginsenoside Rg3, sophorose [β-D-glucopyranosyl (1→2)-β-glucopyranoside], or the aglycone (protopanaxadiol), on their own or in combination had no effect on I Na. These observations indicate that the carbohydrate portion of ginsenoside Rg3 plays an important role in its effect on the Na + channel. ？KSMCB 2005.
Keywords: aglycone; carbohydrate; ginsenoside Rg 3; glucose; hydrazide derivative; protein subunit; RNA; sodium channel; sophorose; sugar; ginsenoside; ginsenoside Rg 3; glucan; nerve protein; protopanaxadiol; sapogenin; sodium channel; sodium channel, voltage gated, type II, alpha 1; sodium channel, voltage-gated, type II, alpha 1; sophorose; triterpene; animal cell; animal tissue; article; brain tissue; chemical structure; controlled study; drug inhibition; electrode; nonhuman; oocyte; rat; voltage clamp; Xenopus; animal; chemistry; drug effect; nerve cell; patch clamp; physiology; structure activity relation; Animalia; Animals; Ginsenosides; Glucans; Nerve Tissue Proteins; Neurons; Oocytes; Patch-Clamp Techniques; Sapogenins; Sodium Channels; Structure-Activity Relationship; Triterpenes; Xenopus